Adsorptive Removal of Trichloroethylene in Water by Crop Residue Biochars Pyrolyzed at Contrasting Temperatures: Continuous Fixed-Bed Experiments - Ming Zhang; Mahtab Ahmad; Mohammad I. Al-Wabel; Meththika Vithanage; Anushka Upamali Rajapaksha; Hyuck Soo Kim; Sang Soo Lee; Yong Sik Ok (Journal of Chemistry)
Biochar (BC) has attracted great attention as an alternative sorbent to activated carbon (AC). Objective of this study was to determine trichloroethylene (TCE) removal by soybean stover BC pyrolyzed at 300 (BC300) and 700°C (BC700) in continuous fixed-bed column. Columns packed with BC300, BC700, and AC reached breakthrough time in 1.1, 27.0, and 50.7 h, respectively. BC700 had higher TCE adsorption capacity than BC300 due to its higher surface area, nonpolarity, and aromaticity. The sorption capacities of AC (774.0 mg g−1) and BC700 (515.1 mg g−1) were 21.6 and 14.4 times higher than that of BC300 (35.9 mg g−1). The lower desorption rate of TCE from BC300 than BC700 and AC may be attributed to the strong binding/partition of TCE to the noncarbonized part of BC. Thomas model also adequately described the adsorption data indicating interphase mass transfer. Overall, AC showed best efficiency for removing TCE from water in column experiments. However, although sorption and desorption capabilities of BC700 were a little lower than AC, it is still a good alternative for AC to remove organic contaminants such as TCE from water due to its cost-effectiveness.